Non-atypical endometrial hyperplasia: risk factors for occult endometrial atypia and malignancy in patients managed with hysterectomy - Lee Shi Hui; Selina Hui Men Chin; Charissa Goh; Lin Xiao Hui; Manisha Mathur; Timothy Lim Yong Kuei; Felicia Chin Hui Xian (Korean Society of Obstetrics and Gynecology, 2021)
Objective To determine the risk factors for occult endometrial atypia and malignancy in patients diagnosed with non-atypical endometrial hyperplasia (NEH) on endometrial biopsy. Methods All new cases of NEH diagnosed between April 2015 and March 2016 at KK Women's and Children's Hospital, who underwent hysterectomy as first-line treatment, were included in the study. Patients with a history of endometrial hyperplasia or malignancy were excluded from the study. Patient demographics (e.g., age, parity, body mass index [BMI]), medical history, and clinical presentation were obtained for analysis. Results In total, 262 patients were diagnosed with NEH, of which 18.3% (n=48) underwent hysterectomy as first-line management. The average time to surgery was 77.0±35.7 days. All cases were diagnosed by dilation and curettage, and hysteroscopy. The mean age was 51 years, and the mean BMI was 26.9±5.8 kg/m2. Histology from the hysterectomy specimen showed 9 (18.8%) patients with atypical hyperplasia and 2 (4.2%) with grade 1, stage 1A endometrioid adenocarcinoma. Patients with higher grade final pathology had significantly lower median parity (1 vs. 2, P=0.039), higher mean BMI (30.1±6.5 vs. 25.9±5.3 kg/m2, P=0.033), and BMI ≥30 kg/m2 (54.5% vs. 13.5%, P=0.008, odds ratio 7.68), compared to patients whose final histology showed NEH or no residual hyperplasia. Conclusion Occult endometrial atypia and malignancy were found in 18.8% and 4.2% of patients with an initial diagnosis of NEH, respectively. High BMI and low parity were identified as significant risk factors for high-grade endometrial lesions in patients with NEH.